2022
DOI: 10.3390/biology11121709
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ecological Factors on the Metabolomic Composition of Fish Lenses

Abstract: Multiple stressors related to changes in environmental conditions (such as water temperature, salinity, and natural and anthropogenic pollution) may cause biological responses of aquatic organisms that lead to significant variations in the biochemical reactions in their tissues and thereby change the concentrations of metabolites. We used a quantitative NMR-based metabolomic analysis of the fish lens for the evaluation of the influence of environmental factors on metabolic processes in aquatic animals. For thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The most season-affected metabolites are osmolytes and antioxidants, and the most affected metabolic pathway is the histidine pathway. We have also studied the influence of ecological factors on the metabolomic composition of lenses of three fish species [37] (Experiment #119). We found that increased water acidity due to CO 2 emissions and reduced DO caused significant changes in the fish lenses' metabolomic compositions, including amino acids, organic acids, and energy metabolites.…”
Section: Database Application Examplesmentioning
confidence: 99%
“…The most season-affected metabolites are osmolytes and antioxidants, and the most affected metabolic pathway is the histidine pathway. We have also studied the influence of ecological factors on the metabolomic composition of lenses of three fish species [37] (Experiment #119). We found that increased water acidity due to CO 2 emissions and reduced DO caused significant changes in the fish lenses' metabolomic compositions, including amino acids, organic acids, and energy metabolites.…”
Section: Database Application Examplesmentioning
confidence: 99%